Vitamin D diminishes the high platelet aggregation of type 2 diabetes mellitus patients. (2nd January 2019) - Sultan, Maya; Twito, Orit; Tohami, Tali; Ramati, Erez; Neumark, Eran; Rashid, Gloria
Abstract: Platelet activation is found in inflammatory conditions and implicated in the pathogenesis of chronic medical conditions, such as atherosclerosis, coronary vascular disease, cerebrovascular disease, and diabetes mellitus (DM). HbA1c is inversely related to vitamin D25 levels in individuals with and without DM. This study aimed to determine the relation between platelet aggregation, vitamin D and HbA1c among healthy individuals and those with Type 2 DM (T2DM). The direct effect of vitamin D1, 25 (calcitriol) on platelet aggregation was also investigated. The study included four groups: A. normoglycemic Control group: HbA1c<5.7%; B. Pre-diabetes (DM): 5.7% ≥ HbA1c ≤ 6.4%; C. DM on aspirin therapy: HbA1c>6.4%(+)Asp.; and D. DM not on aspirin therapy: HbA1c > 6.4%(−)Asp. Platelet aggregation was tested with and without calcitriol or saline pre-treatment, using collagen or adenosine diphosphate (ADP) as agonists. Platelet aggregation was higher in DM(−)Asp group compared to normoglycemic and DM(+)Asp, and higher, but not significant compared to pre-DM. The entire study population exhibited negative correlation between HbA1c and serum concentration of vitamin D25. Excluding DM(+)Asp, aggregation induced by collagen was significantly higher in patients with insufficient (<76 nmol/L) vitamin D25 compared to sufficient (≥76 nmol/L) vitamin D25. In this cohort, a negative correlation was found between serum concentrations of vitamin D25 and collagen-induced percent maximum (%max) aggregation and area under curve (AUC) aggregation. In the DM(−)Asp group, collagen-induced aggregation was reduced by approximately 25% after calcitriol treatment. Calcitriol decreased ADP-induced aggregation of control and DM(+)Asp groups to approximately 85% of saline treatment. We conclude that glycemic control is inversely associated with high platelet aggregation and low vitamin D25 levels. This elevated aggregation could be regulated by a novel, direct effect of calcitriol, indicating a beneficial effect of vitamin D on vascular complications related to diabetes. We offer a possible non-genomic mechanism for the vitamin D/Vitamin D receptor (VDR) pathway.